FINANCIAL DISTRESS DURING THE PANDEMIC: DO FINANCIAL LITERACY AND FINANCIAL COPING BEHAVIOR MATTER? - Sari, Ratna Candra; Priantinah, Denies; Aisyah, Mimin Nur; Sari, Annisa Ratna; Dewayanti, Patriani Wahyu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.09.TAHUN.2022DO - 10.24843/EEB.2022.v11.i09.p12, 2022)
The COVID-19 pandemic is not only related to health problems but also related to life problems across multi-dimensional aspects including economic aspects. The pandemic has led to recession and financial distress for vulnerable groups. The current phenomenon shows that teenagers have a low level of financial literacy and are a psychologically vulnerable group. This study aims to: first, examine the effect of financial socialization agents, which have the potential to impact the level of financial literacy in teenagers. The second objective was to examine the effect of financial literacy on financial emergencies during the pandemic. The extent of the financial distress has a negative impact on the health and performance of the students (not attending classes and poor academic performance). The third goal of this research is to examine the effect of financial literacy and financial distress on coping behaviors. This study used 206 respondents. Hypothesis testing with structural equation modeling using Partial Least Squares (PLS). Based on the results of the factor analysis test, parents and family, people other than parents (teachers and financial professionals), and formal education are the financial socialization agents that affect financial literacy. The results of this study find empirical evidence that financial literacy has a negative impact on financial distress, and that financial literacy has a significant negative impact on financial distress, both directly and through coping behaviors. Implications and suggestions for future research are also suggested.